2016
DOI: 10.1017/s1368980016001853
|View full text |Cite
|
Sign up to set email alerts
|

Declines in traditional marine food intake and vitamin D levels from the 1960s to present in young Alaska Native women

Abstract: Objective To measure the trends in traditional marine food intake and serum vitamin D levels in Alaska Native women of childbearing age (20–29 years old) from 1960 to the present. Design We measured a biomarker of traditional food intake, the δ15N value, and vitamin D level, as 25(OH)D3 concentration, in 100 serum samples from 20–29 year old women archived in the Alaska Area Specimen Bank, selecting 25 per decade from the 1960s to 1990s. We compared these to measurements of RBC δ15N values and serum 25(OH)D3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…Higher consumption of non-traditional foods, as well as the more sedentary lifestyle that corresponds with movement away from traditional subsistence practices, has been linked to health problems such as obesity, diabetes, colorectal cancer, cardiovascular disease, and developmental disorders [65,70,76,77] and to nutritional deficiencies. For example, in the Yukon-Kuskokwim Delta of Alaska, a retrospective study of banked samples from young Alaska Native women taken from 1960 to 2010 showed a significant decline in plasma vitamin D concentrations associated with a drop in the consumption of traditional marine foods [78][79][80]. The prevalence of lifestyle-associated diseases has been increasing in remote communities throughout the circumpolar North.…”
Section: One Health In the Subsistence Contextmentioning
confidence: 99%
“…Higher consumption of non-traditional foods, as well as the more sedentary lifestyle that corresponds with movement away from traditional subsistence practices, has been linked to health problems such as obesity, diabetes, colorectal cancer, cardiovascular disease, and developmental disorders [65,70,76,77] and to nutritional deficiencies. For example, in the Yukon-Kuskokwim Delta of Alaska, a retrospective study of banked samples from young Alaska Native women taken from 1960 to 2010 showed a significant decline in plasma vitamin D concentrations associated with a drop in the consumption of traditional marine foods [78][79][80]. The prevalence of lifestyle-associated diseases has been increasing in remote communities throughout the circumpolar North.…”
Section: One Health In the Subsistence Contextmentioning
confidence: 99%
“…Stable isotope ratios have been validated for use as dietary biomarkers based on three types of work: first, controlled feeding studies, mostly conducted in animals, but in some cases also in humans; second, observational studies in free‐living populations; and finally, large‐scale global surveys . Nevertheless, additional validation studies are necessary if stable isotope biomarkers are to reach their full potential.…”
Section: Scientific Backgroundmentioning
confidence: 99%
“…These effects are likely to have greatest impacts on the traditional diets of people living in low-resource settings. The demise of traditional dietary practices will have health implications such as have been documented by O'Brien et al (2017). That report showed a rise in the prevalence of vitamin D-deficiency rickets among indigenous native populations in Alaska whose diets had shifted from the traditional sources of marine-based food to more processed foods.…”
Section: Impacts On Fisheriesmentioning
confidence: 98%